Respuestas
Respuesta dada por:
8
Hola Chitin, seria asi:
![\frac{3}{4x}= \frac{5}{8} \frac{3}{4x}= \frac{5}{8}](https://tex.z-dn.net/?f=+%5Cfrac%7B3%7D%7B4x%7D%3D+%5Cfrac%7B5%7D%7B8%7D++)
![3= (\frac{5}{8}) *4x 3= (\frac{5}{8}) *4x](https://tex.z-dn.net/?f=3%3D+%28%5Cfrac%7B5%7D%7B8%7D%29+%2A4x)
![3= \frac{20x}{8} 3= \frac{20x}{8}](https://tex.z-dn.net/?f=3%3D+%5Cfrac%7B20x%7D%7B8%7D)
![24 = 20x 24 = 20x](https://tex.z-dn.net/?f=24+%3D+20x)
![x= \frac{24}{20} = \frac{6}{5} x= \frac{24}{20} = \frac{6}{5}](https://tex.z-dn.net/?f=x%3D+%5Cfrac%7B24%7D%7B20%7D+%3D++%5Cfrac%7B6%7D%7B5%7D+)
Saludos.
Saludos.
Respuesta dada por:
1
Respuesta:da 6/5
Explicación paso a paso:
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años